Study of microstructure of physically modified starches to justify the use in sauce technology - Андрєєва, Світлана Сергіївна; Колесникова, Марина Борисівна (Eastern-European Journal of Enterprise Technologies, 2014)
The results of studies of the microstructure of physically modified starches are discussed in the paper. Data on the gelatinization dynamics of physically modified starches from the impact of technological factors (heat treatment duration, pH change) were experimentally obtained. Fractional composition of starches, which are characterized by monodispersity of starch grains was investigated and substantiated. According to the particle size distribution of starch grains, PMS from waxy maize “Endura” and tapioca “Indulge” are optimal in terms of monodispersity. Experimental data and theoretical principles on the rheological properties of starches allow to assess the gelatinization dynamics at the microscopy level. The results obtained indicate the possibility to use physically modified starches, which meet the functional and technological properties of thickeners, in particular, thermal and acid stability. The results obtained are the basis for developing the technology for new food products - sweet sauces based on fruit and berry raw materials using physically modified starches.